The Role of Organizational Culture and Work Discipline in Improving Employee Performance of Regional Public Companies in West Java - Nabilla Dwi Anggraeni Susandi; Imelda Listiani (Universitas KH. Abdul Chalim Mojokerto, 2025)
Using regional public enterprises in West Java as a case study, this research will examine how organizational culture and work discipline affect employee performance improvement (Y). Out of a total of 325 workers, 179 from regional public enterprises in West Java were selected for the study. All of the variables in this study were measured using a Likert scale questionnaire, which is a quantitative approach. Data analysis methods make use of route analysis and descriptive statistics. According to the findings, company culture has a direct and beneficial effect on productivity in the workplace, regarding the correlation between strict workplace discipline and increased productivity.